Evaluating a multi-component intervention to reduce and break up office workers' sitting with sit-stand desks using the APEASE criteria - Marsha L. Brierley; Lindsey R. Smith; Daniel P. Bailey; Samson O. Ojo; David J. Hewson; Sofie A. Every; Taylor A. Staines; Angel M. Chater (BMC, 2022)
Abstract Objective Sedentary workplace interventions have had success in reducing excessive sitting time in office workers, but barriers to implementation and uptake remain. This study formally assessed a theory-derived, sit-stand desk intervention using the APEASE (Acceptability, Practicability, Effectiveness, Affordability, Side-effects, Equity) criteria. Methods Thirteen adults (eight female, mean age 38 ± 10 years) from the treatment arm of a sedentary behaviour intervention participated in semi-structured interviews. Thematic codes were inductively assigned to data items followed by deductive charting using the APEASE criteria. Results The intervention was highly acceptable, practicable, safe to deploy, and helped workers reduce workplace sitting time, though individual preferences and workload mediated engagement. Affordability of sit-stand desks and Equity of access were potential barriers to uptake. Conclusions Through the lens of the APEASE criteria, this theory-derived, multi-component sit-stand desk intervention showed acceptability, practicability and effectiveness in reducing and breaking up sedentary time at work with minimal side effects. Using this approach with further tailoring and personalisation may help workers achieve greater reductions in workplace sitting, though affordability and equity should be considered further.